Experimental Investigation of Viscosity, Enhanced Thermal Conductivity and Zeta Potential of a tio2 Electrolyte – Based Nanofluid - Martinez-Gutierrez, V; Vasco-Calle, D (Elsevier Ltd, 2020)
The development of long-time stable nanofluids for practical use in heat transfer processes is a tremendous scientific challenge because nanoparticles tend to precipitate and agglomerate when in a solution, affecting both their thermophysical properties and their stability. This work experimentally investigates the role of the electro-repulse force by electric charges around the nanoparticle, as a way of improving the stability of an electrolyte-based nanofluid. Nanofluid samples were prepared in a two-step method, with 1 wt% and 3 wt% concentrations (mass fraction) of titanium oxide (TiO2) nanoparticles added to a base fluid consisting of an electrolyte solution with a different concentration of potassium chloride (KCl) and deionized water. The pH of the base fluid was maintained constant, adding HEPES as a buffering agent. The stable condition of the nanofluid was established when the temporal variation of the thermal conductivity was negligible. When stability was established, the dynamic viscosity, zeta potential and the enhancement of the thermal conductivity were measured under controlled temperatures. Experimental results showed that the stable behavior of the nanofluid was directly influenced by the electric charge around the nanoparticles and the electro-repulse force between the nanoparticles (represented by the zeta potential), producing a consistent and homogenous stable condition for an extended 30-day period. Due to the greater number of nanoparticles in the 3 wt% solution, the dynamic viscosity of the nanofluid at 3 wt% was higher than at 1 wt%. It was noted that the addition of the nanoparticles did not affect the Newtonian nature of the fluid (except that it was slightly for higher KCl concentrations) and it produced an increase of a 41.75 ± 2.4% for 1 wt% and 59.32 ± 2.1% for 3 wt% of the nanofluid dynamic viscosity, with respect to that of the pure water. Significant enhancement of thermal conductivity enhancement was also obtained, ranging from 0.46 ± 0.11% to 1.47 ± 0.12% for the 1 wt%; and, 2.15 ± 0.11% to 4.7 ± 0.13% for the 3 wt% of nanoparticles added. This noteworthy improvement was attributed to the higher level of homogeneity of the nanofluid, caused by the high electro-repulse force between nanoparticles. Stable electrolyte-based nanofluids, such as KCl, which increase the electro-repulse forces between nanoparticles, can bolster the application of this type of nanofluid in energy conversion and electronic cooling. Enhanced stability properties (particularly in microchannel heat sinks) give these nanofluids the ability to use electric fields for the fluid motion, rather than traditional pumping devices. © 2020 Elsevier Ltd